Revalidating the religious/spiritually integrated practice assessment scale for educators across four mental health disciplines - Oxhandler, Holly K. (Journal of spirituality in mental health, 2025)
This paper describes the validation of the Religious/Spiritually Integrated Practice Assessment Scale for Educators (RSIPAS-EDU) with a diverse sample of faculty in social work, counseling, marriage and family therapy, and psychology. Full-time faculty at accredited graduate schools across disciplines were invited to participate in an online survey that included the RSIPAS-EDU, and 1,742 completed it. Results support the RSIPAS-EDU as a reliable and valid tool to assess mental health educators’ self-efficacy, attitudes, perceived feasibility, behaviors, and overall orientation toward training students to integrate clients’ religion/spirituality in treatment, and identify faculty development needs. Implications and recommendations for future studies are discussed.